Selected Solutions for Individual Rescue Equipment on Polish Racing Catamarans with Length of 15 Metres - Krajewska, P. (Scientific Journal of Gdynia Maritime University, 2018)
The article proposes rescue equipment for Polish regatta units – catamarans in terms of chances of survival in water while conducting active searches. Selected solutions are presented on the basis of rescue action No. 071/SAR/2017 performed by the Maritime Search and Rescue Service.